Implementation of E-Learning in Schools to Improve Student Skills - Linmasya Syafa’atun Nurjannah; Didik Himmawan (Ilmina: Journal of Education and Counseling, 2025)
This paper aims to determine the effect of the Implementation of E-Learning Learning in Schools to Improve Student Skills. It is hoped that educators and those related to education can maximize this opportunity well so that they can motivate students to learn. This research method is a literature study by collaborating between library research and conducting observations and interviews. The results show that E-Learning Learning is also a very effective learning method for students and teachers because it can be done at any time. Teachers and students can communicate during E-Learning learning via WhatsApp, Telegram, Gmail or other E-Learning learning media such as Google Classroom.